High Altitude - Berger, Marc Moritz; Luks, Andrew M. (Seminars in Respiratory and Critical Care Medicine, 2023)
With ascent to high altitude, barometric pressure declines, leading to a reduction in the partial pressure of oxygen at every point along the oxygen transport chain from the ambient air to tissue mitochondria. This leads, in turn, to a series of changes over varying time frames across multiple organ systems that serve to maintain tissue oxygen delivery at levels sufficient to prevent acute altitude illness and preserve cognitive and locomotor function. This review focuses primarily on the physiological adjustments and acclimatization processes that occur in the lungs of healthy individuals, including alterations in control of breathing, ventilation, gas exchange, lung mechanics and dynamics, and pulmonary vascular physiology. Because other organ systems, including the cardiovascular, hematologic and renal systems, contribute to acclimatization, the responses seen in these systems, as well as changes in common activities such as sleep and exercise, are also addressed. While the pattern of the responses highlighted in this review are similar across individuals, the magnitude of such responses often demonstrates significant interindividual variability which accounts for subsequent differences in tolerance of the low oxygen conditions in this environment.
Keywords: acclimatization; cardiovascular system; exercise; gas exchange; hematologic system; hypoxic pulmonary vasoconstriction; hypoxic ventilatory response; respiratory system